Env-less endogenous retroviruses are genomic superspreaders - Magiorkinis, Gkikas (National Academy of Sciences, 2012)
Endogenous retroviruses (ERVs) differ from typical retroviruses in being inherited through the host germline and therefore are a unique combination of pathogen and selfish genetic element. Some ERV lineages proliferate by infecting germline cells, as do typical retroviruses, whereas others lack the env gene required for virions to enter cells and thus behave like retrotransposons. We wished to know what factors determined the relative abundance of different ERV lineages, so we analyzed ERV loci recovered from 38 mammal genomes by in silico screening. By modeling the relationship between proliferation and replication mechanism in detail within one group, the intracisternal A-type particles (IAPs), and performing simple correlations across all ERV lineages, we show that when ERVs lose the env gene their proliferation within that genome is boosted by a factor of ∼30. We also show that ERV abundance follows the Pareto principle or 20/80 rule, with ∼20% of lineages containing 80% of the loci. This rule is observed in many biological systems, including infectious disease epidemics, where commonly ∼20% of the infected individuals are responsible for 80% of onward infection. We thus borrow simple epidemiological and ecological models and show that retrotransposition and loss of env is the trait that leads endogenous retroviruses to becoming genomic superspreaders that take over a significant proportion of their host's genome.